Severe ulcerative pododermatitis infected with Staphylococcus aureus and Proteus spp in a guinea pig (Cavia porcellus): a case report - Venturo B., Renzo (2021)
A case of severe ulcerative pododermatitis infected with Staphylococcus aureus and Proteus spp in a guinea pig raised in a metal cage is described. A 9-month-old female guinea pig weighing 850 g is taken to consultation for presenting discomfort when walking. Severe ulcerative pododermatitis (grade IV or V) in the hind limbs was diagnosed based on clinical signs, cytology, and radiographs. The animal was removed from the cage and placed on a flat surface. She was treated with a preparation based on 4 g of sugar and 0.5 ml of “dragon’s blood” (Croton lechleri), applying it to the lesion once a day and subsequently bandaging the affected area; in addition, oral prednisolone was used at a dose of 0.8 mg/kg every 24 hours in syrup for 14 days, and subcutaneous gentamicin at a dose of 6 mg/kg every 24 hours for a minimum of 21 days. Weekly clinical and cytology evaluations were made. The patient gradually improved, reducing the lesions, and the number of bacteria and inflammatory cells. The ulcers on the left leg closed on day 20 and on the right leg on day 26 of treatment.